2015
DOI: 10.1118/1.4905157
|View full text |Cite
|
Sign up to set email alerts
|

Improved image quality in pinhole SPECT by accurate modeling of the point spread function in low magnification systems

Abstract: Purpose: Single photon emission computed tomography (SPECT) has become an important noninvasive imaging technique in small-animal research. Due to the high resolution required in small-animal SPECT systems, the spatially variant system response needs to be included in the reconstruction algorithm. Accurate modeling of the system response should result in a major improvement in the quality of reconstructed images. The aim of this study was to quantitatively assess the impact that an accurate modeling of spatial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…We used knife-edge apertures, which allowed considerable penetration from the 159 keV photons forming ring-shaped projections and impacting the spatial resolution, as shown in figure 12. These rings can be reduced and hence the spatial resolution can be improved by using keel-edge apertures at the expense of decreased sensitivity (Van Der Have and Beekman 2006) and/or modeling the PSF (Pino et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…We used knife-edge apertures, which allowed considerable penetration from the 159 keV photons forming ring-shaped projections and impacting the spatial resolution, as shown in figure 12. These rings can be reduced and hence the spatial resolution can be improved by using keel-edge apertures at the expense of decreased sensitivity (Van Der Have and Beekman 2006) and/or modeling the PSF (Pino et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Balancing design aspects necessitates tradeoffs between sensitivity and resolution goals, therefore we have generated 14 design iterations of the DC-SPECT with varying geometry, such as detector pixel size, pinhole size, detector to collimator distances, number of detector heads, etc Previous simulation and modelling results [1][2][3] demonstrated that our system can achieve a calculated 10.0 mm FWHM system spatial resolution and 0.07% sensitivity at the center of FOV. Other than the intrinsic system resolution determined by geometry design, the reconstructed image resolution can also serve as a predictor of the prospective system performance and can be improved by applying iterative algorithms with resolution recovery methods [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Analytical methods can be used to cycle through design iterations but lack accurately reconstructed images without a MC simulated system matrix. Compensating the mismatch between analytic calculation and the acquired data by involving PSF modelling is an option to balance the computation efforts and the accuracy of system matrix modelling [6,7,10,11], and has shown improvement of the image quality [4,12]. The resolution recovery methods based on PSF are usually proposed for modelling the depth of interaction [13], the finite collimator resolution [14], and the detector blurring as well as the misalignment between the pinhole and aperture [8], and is often modelled as a 2D/3D Gaussian [15,16], or Gaussian plus exponential function or B-spline [17].…”
Section: Introductionmentioning
confidence: 99%